PENGARUH FEE AUDIT, INDEPENDENSI, PENGALAMAN AUDITOR DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT (STUDI KASUS KAP DI JAWA TIMUR) - Fauziah, Katherine; Dwinda Yanthi, Merlyana (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
The research aims to obtain evidence of the effect of audit fees, independence, work experience and competence on audit quality. This research conduct at a Public Accountant Office in East Java registered in IAPI (Institut Akuntan Publik Indonesia) 2020. The method of determining the sample uses purposive sampling method. The data collection method uses a questionnaire. The research used multiple linear regression for analysis technique and using the SPSS V.26 application. The results explain that audit fees, independence and competence has a positive effect on audit quality. Meanwhile, work experience has no effect on audit quality.